Conflicting gender-related differences in the natural history of patients with Idiopathic Dilated Cardiomyopathy. - Laura Vitali Serdoz; Cristina Lutman; Elena Cadamuro; Giulia Barbati; Massimo Zecchin; Marco Merlo; Ilaria Puggia; Bruno Pinamonti; Andrea Di Lenarda; Gianfranco Sinagra (Epidemiology, Biostatistics and Public Health)
Objective. To evaluated possible clinical and instrumental, natural history and prognostic divergences in women and men with idiopathic dilated cardiomyopathy (IDCM). Patients and Methods. From 1988 to 2012, we evaluated 803 consecutive patients with IDCM recorded in the Heart Muscle Disease Registry of Trieste (Italy). All patients had serial follow-up evaluations at 6, 12, and 24 months, and subsequently every two years, or more frequently if clinically indicated. Results. Two hundred and twenty-seven patients (28%) were female. At first evaluation women were significantly older (48 vs. 45 years old, p = 0.008); presented more frequently left bundle branch block at ECG (38% vs. 28%, p = 0.01), smaller left ventricular end-diastolic indexed volume at echocardiography (85 vs. 93 ml/m2, p <0.002) and more frequently moderate to severe mitral regurgitation at Doppler (43% vs. 33%, p = 0.015). No differences in NYHA class, medical treatment and device implantation rates were found. During a median of 108 months follow-up, women showed a significantly lower ten-year total mortality/heart transplantation (20% vs. 32% respectively, p = 0.001) and cardiovascular mortality rates (9% vs. 15%, p = 0.024) despite a less marked clinical and echocardiographic improvement. Conclusions. In our population of patients with IDCM, women showed a better long-term prognosis notwithstanding a presentation with a more advanced disease and a lower clinical-instrumental improvement on optimal medical therapy compared to men.